Default on Rental Renting a Car at Hidro Rent Car and Tour Jogja - Windarwoko, Muhammad Gibran; Heriyani, Endang (JUPE : Jurnal Pendidikan Mandala, 2024)
Not everyone can have a private vehicle, so it needs a car to rent because it provides transportation options for people to reach places like recreation, hiking, or traveling. It's because of the efficiency of cars, which can transport people.  Hidro Rent Car And Tour Jogja is one of the companies in the field of car rental.  The purpose of this research is to find out the form of the misrepresentation and its conclusion in the car rental agreement at Hidro Rent Car. The type of research used is a combination of normative legal research and empirical legal research, so that the research data consists of primary data and secondary data. The conclusion of this investigation: (1) the form of discharge performed by the tenant is to damage the rental car and to be late in returning the rented car. (2) The discharges performed are that the tenants are obliged to replace the loss by paying compensation money, and the deposit money used to pay the car service fee, as well as paying the daily fee while the car is in the workshop until the car can be reused as it used.